THE EFFECTIVENESS OF DICTATION METHOD TOWARD STUDENTS’ ABILITY IN WRITING RECOUNT TEXT OF EIGHTH GRADE AT SMP NEGERI 37 MEDAN - Friska Damayanti Sitorus; Fenty Debora Napitupulu; Sahat Taruli Siahaan (Jurnal Scientia, 2023)
The objective of the study is intended to find out the effect of Dictation Method on students" writing skill in SMP Negeri 37 Medan. The research design used in this study was experimental quantitative design. The population of this study is the Grade VIII students of SMP Negeri 37 Medan with two classes, and there are VIII-A & VIII-B. The sample of the research is two classes (VIII A & B), that selected by using random sampling. The sample is divided into two groups; the first group is 30 students as the experimental group. The second group is 30 students as the control group. The instrument used for collecting the data was test in the form essay writing with choose a topic that has been prepare. The tests are divided into two: pre-test and post-test. The data was analyzed by using t-test formula in order to see whether the Dictation method affects students' writing skill. The result of the analysis shows that t- test (3,84), it is higher than the t-table (2.048) with the level of significant (0,05) and the degree of freedom (df) (58). The result of the analysis shows that the alternative hypothesis (Ha) of the study is accepted and the null hypothesis (Ho) is rejected because t-test > t-table (3.84 > 2.048). From the data presented, it can be concluded that there is an effect of using dictation method on students’ writing ability in class VIII students of SMP Negeri 37 Medan in the 2022/2023 Academic Year.